Health Condition of Hard Corals on Rote Island in The Sawu National Park Conservation Area - Mikael Prastowo Sesotyo Widodo; Fakhrurrozi; Rifky Nur Fahmi; Cakra Adiwijaya; Ayu Adhita Damayanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Rote Ndao waters are known as a source of diversity of coral reefs in TNP Laut Sawu. Coral reefs in the area suffered considerable damage due to human activities. This study aims to determine the latest health conditions of the coral reef area in the northern region of Rote Island. Data monitoring was carried out using the underwater photo transect (UPT) method at 12 stations in the north of Rote Island. The percentage of coral reef bottom substrate cover was obtained by processing photo data using the Coral Point Count with Excel Extension-CPCe application. In addition, an assessment of the benthic component was also carried out based on the categories of percentage cover of fleshy seaweed, cover of rubble and hard coral. The results show condition of coral reefs based on percent cover is in the low category with a hard coral (HC) value of 9.02 ± 7.16%. The highest average value of hard coral cover was found at the Tesabela station. The three highest mean values for the bottom substrate cover type at the observation sites were dead coral with algae (DCA) 32.91 ± 19.5%; Algae assemblage (FS) 17.50 ± 19.27% and Sand (S) 17.43 ± 8.91%. The health condition of coral reefs based on the benthic component shows that the coral reef ecosystem is in a damaged condition and it is difficult to recover if it is disturbed. Necessary to carry out good and efficient management in the future, namely by reducing human activities without causing damage to coral reefs and finding ways for the community to continue to benefit economically from coral reef areas in the Sewu Marine National Park.